Professional English Teacher Competence and Its Relation to 21st Century Skills and Learning - Melliofatria, Melliofatria; Jannatul Jannah, Wirda; Corrina, Fatti (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study is to find out what the teacher's duties are and what competencies a teacher must have because the challenges of the 21st century demand many things so that the teacher becomes someone who has multiple roles. The method used in this study is the systematic review method. The results obtained are that in the 21st century, the role of a teacher is to renew the quality of learning, assist students in developing participation, make adjustments to personalized learning, emphasize project and problem-based learning, and motivate students to work together and communicate.